Study on income settlement basis of server board public beneficiaries of transition regime - Reyes Sarmiento, Lina Marcela; León Chaín, María Carolina; Noriega Jaime, Luz Adriana (DIXI, 2019)
Objective: the regulation of the pension system of public employees over the years has been subject to constant structural changes in order to ensure fiscal sustainability, which has brought the issuance of several rules and abundant jurisprudence on the subject. Methodology: in this article the jurisprudential changes presented in the interpretation are analyzed of the amount of the old-age pension to public servants covered by the transition regime. Findings: the conflict between the principles that favor pension rights is highlighted and the principles and criteria that seek the protection of the social security system in Colombia. Conclusions: it is concluded that, under the argument of achieving fiscal sustainability, they cannot be impaired the fundamental rights or legitimate expectations of public employees with the adoption of measures regressive that limit the materialization of a better pension, and, if done, this should be better justified, in order to ensure the legitimacy of judicial unification decisions.